2018
DOI: 10.1186/s40352-018-0072-7
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and community justice

Abstract: BackgroundThere has long been concern about the number of people who die in custody in England and Wales, particularly in prisons or police stations. The concern is obviously heightened when people die either at their own hand, or at the hands of others. Yet there has been selective critical gaze, and people who die whilst under probation or community supervision have been neglected (Phillips, J, Gelsthorpe, L, Padfield, N., Criminology & Criminal Justice, 10.1177/1748895817745939, 2017). Given that there is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Improving the mental health and wellbeing of prisoners is a complex task and it is essential that the risk factors for poor mental health and wellbeing in prison are understood (Phillips et al 2018). This study has aimed to identify associations between ACEs and lifetime mental illness diagnosis, self-harm or suicide attempt in incarcerated males, and to explore if ACEs predict current low MWB in prison.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the mental health and wellbeing of prisoners is a complex task and it is essential that the risk factors for poor mental health and wellbeing in prison are understood (Phillips et al 2018). This study has aimed to identify associations between ACEs and lifetime mental illness diagnosis, self-harm or suicide attempt in incarcerated males, and to explore if ACEs predict current low MWB in prison.…”
Section: Discussionmentioning
confidence: 99%
“…People who are under the criminal justice system in community settings also have a higher rate of suicidal ideas, thoughts and suicide when compared to the general population, particularly those aged between 30 to 59 years old. Suicide rates peak within two weeks, and remain high for up to six weeks, after of receiving a community order (Phillips, Padfield, & Gelsthorpe, ). The population who are under the criminal justice system in all settings are a high risk populations requiring special attention in suicide prevention strategies.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…In the absence of data showing any analysis by age-which could be useful to further our understanding of what is happening- Table 3 uses 2015-16 data from previous research to show that the risk of dying by suicide for women under all forms of probation supervision is between 50 and 86 times higher than the suicide rate amongst women in the general population. 10 There has been a longstanding debate about how best to deal with women who are convicted of an offence. Research has shown that putting women in prisons that were designed 'by men and for men' does little more than perpetuate women's prior experiences of structural inequality and personal violence.…”
Section: Post-custody Deathsmentioning
confidence: 99%